In the language of works and tourist travels: to the 70th anniversary of doctor of economic sciences, professor Heorhiy Pavlovich Sklyar - Lyman, Serhii (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Міжнародні відносини, економіка, країнознавство, туризм, 2024)
The article examines the biography and scientific and pedagogical activity of the famous higher education teacher, professor, administrator, public figure G. P. Sklyar, who turned 70 this year. The scientist made his main contribution to science in such areas as tourism and the economic potential of consumer cooperative trade enterprises. This is the subject of G. P. Sklyar's fundamental research, including his doctoral dissertation "Economic conditions and contradictions in the development of consumer cooperation in a transition economy". G. P. Sklyar is an experienced administrator and manager, dean of the faculty of advanced training, director of the Intersectoral Institute for Advanced Training and Retraining of Specialists, head of the Department of Tourism and Hotel Business at the Poltava University of Economics and Trade. Longterm scientific, pedagogical, social, administrative activity of G. P. Sklyar contributed to the development of Ukrainian science and the training of new personnel for the economy and tourism sector of Ukraine. science and the training of new personnel for the economy and tourism sector of Ukraine.